Observasi Keragaan Ukuran Benih, Endosperma, dan Embrio Genotipe Padi (Oryza sativa L.) Tropis dengan Image Analysis: Observasi Keragaan Ukuran Benih, Endosperma, dan Embrio Genotipe Padi Tropis (Oryza sativa L.) dengan Image Analysis - Fauzi, Ahmad Rifqi; Junaedi, Ahmad; Lubis, Iskandar; Ghulamahdi, Munif; Aswidinnoor, Hajrial (Universitas Bangka Belitung, 2024)
Rice is important staple food in the world. One important input in rice production is seed vigor, is determined by seed characteristics such as seed size and shape. The Digital image processing could facilitate observations of seed size faster, large samples, produce accurate, and robust data. However, this study was designed to investigate size of seed, endosperm and embryo of 55 tropical rice genotypes using image analysis and correlation anlysis between characters. A total of 400 seeds, 40 endosperms, and 8 embryos containing each genotype were investigated for their size characteristics. The results of the investigation showed that genotype differences had a significant effect on size of seed, endosperm and embryo. The length of tropical rice seeds is included in the medium-very long seeds and has a significant positive correlation (α <0.01) with the weight of 1000 grain grains, seed area, shape of the seed (length-to-width ratio), and endosperm length. Embryo size characters (length, width, area, and circumference) have a significant positive correlation (α <0.05) with seed area. The results can be considered in the crop improvement of tropical rice plants in the future.